Report of the Work of the National Joint Committee for Spanish Relief, The British Committee for Refugees from Spain and The Basque Children's Committee (1939)
1939 038-0069-011 Please cut out this coupon and send it with your Cheque or Postal Order to: The Secretary, National Joint Committee for Spanish Relief, 30 Eccleston Street, London, S.W.1. I enclose herewith a donation of £ : : , which I would like to be used for the Refugee Fund. the Basque Children.* Please send the receipt to Name (block letters).......................... ....................... Address ............................................................... Cheques and Postal Orders should be made payable to National Joint Committee for Spanish Relief. * Cross out whichever is inapplicable. Please cut out this coupon and send it to: The Secretary, Basque Children's Committee, 30 Eccleston Street, London, S.W.1. I am willing to offer free hospitality to a Basque child until it can be restored to its parents. I should like a boy girl * of ............... years. Name (block letters)...................................................... Address * Cross out whichever is inapplicable. 292/946/38/69(XI)